ANALISIS FAKTOR –FAKTOR MOTIVASI EKSTERNAL DAN INTERNAL YANG MEMPENGARUHI PRODUKTIVITAS KERJA (Studi Kasus : UD. Pia Bali Sinar Abadi) - Dewi Laksmi, Dewa Ayu Candra; Tuningrat, I.A. Mahatma; Suryawan Wiranatha, A.A.P.Agung (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 2 (2016): Juni)
Motivation is willingnessto make efforts to achieve organizational goals conditioned by the effort's ability to meet the needs of a particularindividual. The purposes of this study were to determine : (i) the factorsof external and internal motivation that can affect employee productivity and (ii) the motivation factors that are the most dominant influencing employee productivity at UD. Pia Bali Sinar Abadi. This study used primary data was obtained fromrespondents through questionnaires. The collected data was analysed byusing factor analysis. The results show that there ware six factors of external motivation, namely physical work environment, remuneration, status, implementation and administration of the company, social work environment, supervision and three factors of internal motivation namely the work itself, responsibility, and achievement significantly influenced employee productivity at UD. Pia Bali Sinar Abadi. The most dominant factor influenced the employeeproductivity in UD. Pia Bali Sinar Abadi wasfactor of responsibility withextraction value of 0.819. Keywords: work motivation, work productivity, factor analysis.
Keywords: 94,